Orbital metastases in Italy - Magliozzi, Patrizio (Int J Ophthalmol, 2015)
AIM: To describe a series of Italian patients with orbital metastasis focusing on the outcomes in relation to the different primary site of malignancy. METHODS: Retrospective chart review of 93 patients with orbital metastasis collected in a tertiary referral centre in a period of 38y and review of literature. RESULTS: Out of 93 patients, 52 were females and 41 were males. Median age at diagnosis was 51y (range 1 to 88y). The patients have been divided into four groups on the basis of the year of diagnosis. The frequency of recorded cases had decreased significantly (P<0.05) during the last 9.5y. Primary tumor site was breast in 36 cases (39%), kidney in 10 (11%), lung in 8 (9%), skin in 6 (6%); other sites were less frequent. In 16 case (17%) the primary tumor remained unknown. The most frequent clinical findings were proptosis (73%), limited ocular motility (55%), blepharoptosis (46%) and blurred vision (43%). The diagnosis were established by history, ocular and systemic evaluation, orbital imaging studies and open biopsy or fine needle aspiration biopsy (FNAB). Treatment included surgical excision, irradiation, chemotherapy, hormone therapy, or observation. Ninety-one percent of patients died of metastasis with an overall mean survival time (OMST) after the orbital diagnosis of 13.5mo. CONCLUSION: Breast, kidney and lung are the most frequent primary sites of cancer leading to an orbital metastasis. When the primary site is unknown, gastrointestinal tract should be carefully investigated. In the last decade a decrease in the frequency of orbital metastasis has been observed. Surgery provides a local palliation. Prognosis remains poor with a OMST of 13.5mo ranging from the 3mo in the lung cancer to 24mo in the kidney tumor.